Governmentalities of Urban Crises in Inner‐city Athens, Greece. Issue 1 (23rd June 2015) - Koutrolikou, Penny (Panagiota)
Abstract: Through the notion of "conjuncture" this paper explores the interplay of urban crises that have been unfolding in the city of Athens during the past 7 years (2008–2014). By focusing on specific "critical moments" that have significantly influenced the narratives, discourses and subsequent policies concerning "Athens in crisis", it examines a number of intertwined approaches and tactics that shaped the governmentality of such crisis. These approaches and tactics, that work in tandem, include emergency‐driven policies and politics; politics of fear that occasionally transform into geographies of fear; processes of defining the "public" and "public enemies"; and redefinitions of (il)legalities. Yet, they have repercussions on people, places and politics. In this context, certain issues are deemed critical or urgent while others do not or are even obscured.